Resistência de genótipos de cana-de-açúcar ao Sugarcane mosaic virus (SCMV) - Silva, Marcel Fernando da [UNESP] (2014)
The resistance to diseases constitutes the main factor of cultivar replacement in sugarcane, being mosaic one of the main diseases of this crop, with records in almost all the major sugarcane growing countries. This study aimed to evaluate the resistance of 79 sugarcane genotypes, including varieties and elite clones, artificially inoculated with Sugarcane mosaic virus (SCMV) R1b-1 and estimate genetic parameters associated to mosaic resistance by variance analysis. Evaluations of symptoms by grade scale associated with serological test Plate Trapped Antibody-ELISA were performed in a greenhouse experiment that was later taken to field conditions. The genotypes IACSP982053, IACSP972028, RB855156, IACSP993009, IACSP977543, IACSP972000, IACSP962100, IACSP986202, IAC912195, IACSP953028, IAC862480, IACSP972098, IACSP955000, SP701143, IACSP952078, IACSP972020, IACSP967569, IACSP985046, SP803280, IACSP993085, IACSP972055 and IACSP977065 were resistant to the strain in study. The broad-sense heritability at individual level and means based was 19.37% and 62.18%, respectively, which shows a great influence of environmental conditions on the expression of mosaic symptoms. Wild sugarcane germplasm were also evaluated for SCMV resistance in a second experiment, in order to identify new sources of mosaic resistance for future introgression crosses. An evaluation of symptoms by grade scale associated with serological test Plate Trapped Antibody-ELISA were performed for 43 clones, including Saccharum officinarum, S. barberi, S. spontaneum and S. robustum species, maintained under natural infection conditions. The clones IS76-155, IJ76-418 red, NG57-50, Ceram red, Badila, Sac.off. 8276, Fiji19 IJ76-313, US 57-141-5, Krakatau, IN8458, IN84-88, IN84-82, Gandacheni and Chin possibly represents resistant sources. A differential behavior among Saccharum species were also observed, with higher susceptibility in ...